The Relationship Between the Big Five Personality Traits and Self-Regulated Learning Strategies Among University Student in Learning TOEFL Preparation - Yudha Aprizani; Fitra Ramadani; Hartatya Novika; Andini Septama Sari (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
The study portrays university-students’ personality traits concerning about their self-regulated learning during learning TOEFL preparation. This study examines the correlation between personality trait and self-regulated learning experienced by university-students during learning TOEFL Preparation. A total of 113 University-students are participated in this study. This study conducts online survey questionnaire for data collection. The Self-Regulation Questionnaire (SRQ) model developed by Brown et al., (1999) is employed to measure self-regulated learning during participated in learning TOEFL preparation. Moreover, the study The Big-Five Personality Inventory (BFPI) to measure university-students’ personality traits developed by Soto and John (2017). The result of this study shows that the correlation between the students’ personality traits and their self-regulated learning will gain a significant impact for the University-students in encountering their preparation in TOEFL test. This study is expected to be able to help the university students to be aware of how to overcome their difficulties to regulate their personality traits in encountering a process of learning TOEFL preparation.